Investigating the crucial roles of aliphatic tails in disulfide bond-linked docetaxel prodrug nanoassemblies - Yuequan Wang; Cong Luo; Shuang Zhou; Xinhui Wang; Xuanbo Zhang; Shumeng Li; Shenwu Zhang; Shuo Wang; Bingjun Sun; Zhonggui He; Jin Sun (Elsevier, 2021)
Disulfide bond-bridging strategy has been extensively utilized to construct tumor specificity-responsive aliphatic prodrug nanoparticles (PNPs) for precise cancer therapy. Yet, there is no research shedding light on the impacts of the saturation and cis-trans configuration of aliphatic tails on the self-assembly capacity of disulfide bond-linked prodrugs and the in vivo delivery fate of PNPs. Herein, five disulfide bond-linked docetaxel-fatty acid prodrugs are designed and synthesized by using stearic acid, elaidic acid, oleic acid, linoleic acid and linolenic acid as the aliphatic tails, respectively. Interestingly, the cis-trans configuration of aliphatic tails significantly influences the self-assembly features of prodrugs, and elaidic acid-linked prodrug with a trans double bond show poor self-assembly capacity. Although the aliphatic tails have almost no effect on the redox-sensitive drug release and cytotoxicity, different aliphatic tails significantly influence the chemical stability of prodrugs and the colloidal stability of PNPs, thus affecting the in vivo pharmacokinetics, biodistribution and antitumor efficacy of PNPs. Our findings illustrate how aliphatic tails affect the assembly characteristic of disulfide bond-linked aliphatic prodrugs and the in vivo delivery fate of PNPs, and thus provide theoretical basis for future development of disulfide bond-bridged aliphatic prodrugs.